Performance of the Parasympathetic Tone Activity (PTA) index to assess the intraoperative nociception using different premedication drugs in anaesthetised dogs. Issue 1 (1st January 2020) - Mansour, Christelle; El Hachem, Nour; Jamous, Patrick; Saade, Georges; Boselli, Emmanuel; Allaouchiche, Bernard; Bonnet, Jeanne-Marie; Junot, Stéphane; Chaaya, Rana
ABSTRACT: The dynamic variations of the Parasympathetic Tone Activity (PTA) index were evaluated to assess nociception in dogs undergoing anaesthetic protocols with different premedication drugs. Sixty-six dogs, divided into three groups of 22 dogs each, were given different premedication drugs "morphine" (0.2 mg/kg), "morphine + medetomidine (5 μg/kg)", "morphine + acepromazine (0.03 mg/kg)", then similarly induced and maintained under general anaesthesia. The PTA, HR (heart rate) and MAP (mean arterial pressure) were assessed at S (steady-state), Cut (cutaneous incision), PTAE (PTA Event, assessed 1 min before a significant PTA decrease), HDR (Haemodynamic reaction, assessed 5 min before an increase of ≥ 20% in HR and/or MAP). For each group, the dynamic variation of PTA (ΔPTA) was calculated and a Receiver Operating Characteristics (ROC) curve was performed to detect if any of the premedication drugs may alter the performance of PTA index to predict intraoperative haemodynamic reactions. In all groups, a haemodynamic reaction was detected after Cut, PTAE and HDR and was preceded with a significant decrease of PTA, except for "morphine + medetomidine" group which showed a significant drop of PTA only at PTAE and HDR. The ΔPTA showed a fair performance in all groups (a mean [95% CI] AUC of 0.73 [0.62–0.82], 0.70 [0.59–0.79] and 0.71 [0.59–0.80] respectively in morphine, morphine + ACP and morphine + medetomidine). Although ΔPTA was rather altered by the premedication drug, it was able to predict, to a certain extent, haemodynamic reactions in all groups.